SISTEM PEMERINTAHAN DALAM MASA BANI UMAYYAH - Erik Yudistira; M. Eza Helyatha Begouvic; Husni Tamrin (SOL JUSTICIA, 2022)
The Umayyads or the Umaiyah Caliphate was the first Islamic caliphate after the Rashidun Caliphate, which ruled from 661-750 AD in the Arabian peninsula centered in Damascus, Syria, and from 756-1031 in Cordoba-Andalusia, Spain. The period of the Umayyad Caliphate was only 90 years old, starting during the reign of Muawiyah bin Abi Sufyan, where the Islamic government turned into a hereditary kingdom. Namely after Al-Hasan bin 'Ali bin Abi Talib handed over the caliphate to Muawwiyah in order to reconcile the Muslims who at that time were being hit by slander due to the killing of Uthman bin Affan, namely during the Jamal war and the betrayal of the Khawarij and Shia people. This research approach is a juridical-normative research approach. The source of this research data was taken from several existing literature in offline and digital libraries.